Malignancy and viral infections in Sub-Saharan Africa: A review - Diakite, Mahamadou; Shaw-Saliba, Kathryn; Lau, Chuen-Yen (Frontiers in Virology, 2023)
The burden of malignancy related to viral infection is increasing in Sub-Saharan Africa (SSA). In 2018, approximately 2 million new cancer cases worldwide were attributable to infection. Prevention or treatment of these infections could reduce cancer cases by 23% in less developed regions and about 7% in developed regions. Contemporaneous increases in longevity and changes in lifestyle have contributed to the cancer burden in SSA. African hospitals are reporting more cases of cancer related to infection (e.g., cervical cancer in women and stomach and liver cancer in men). SSA populations also have elevated underlying prevalence of viral infections compared to other regions. Of 10 infectious agents identified as carcinogenic by the International Agency for Research on Cancer, six are viruses: hepatitis B and C viruses (HBV and HCV, respectively), Epstein-Barr virus (EBV), high-risk types of human papillomavirus (HPV), Human T-cell lymphotropic virus type 1 (HTLV-1), and Kaposi's sarcoma herpes virus (KSHV, also known as human herpes virus type 8, HHV-8). Human immunodeficiency virus type 1 (HIV) also facilitates oncogenesis. EBV is associated with lymphomas and nasopharyngeal carcinoma; HBV and HCV are associated with hepatocellular carcinoma; KSHV causes Kaposi’s sarcoma; HTLV-1 causes T-cell leukemia and lymphoma; HPV causes carcinoma of the oropharynx and anogenital squamous cell cancer. HIV-1, for which SSA has the greatest global burden, has been linked to increasing risk of malignancy through immunologic dysregulation and clonal hematopoiesis. Public health approaches to prevent infection, such as vaccination, safer injection techniques, screening of blood products, antimicrobial treatments and safer sexual practices could reduce the burden of cancer in Africa. In SSA, inequalities in access to cancer screening and treatment are exacerbated by the perception of cancer as taboo. National level cancer registries, new screening strategies for detection of viral infection and public health messaging should be prioritized in SSA’s battle against malignancy. In this review, we discuss the impact of carcinogenic viruses in SSA with a focus on pathogenesis, epidemiology, and control strategies.